The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s10639-022-10994-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of augmented reality application integration with computational thinking in geometry topics

Abstract: In this article, researchers conducted a study that integrates Augmented Reality application with Computational Thinking into Geometry Topics. Three variables were measured, Computational Thinking, Visualisation Skills and Geometry Topic achievement. The study was implemented with 124 students in two different schools using quasi-experimental study design. The t-test analysis was performed to see the differences before and after the intervention between the control and treatment groups. Next, a MANCOVA was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…Simulation is another essential plugged-in activity, where pupils can utilize computer simulations, including Augmented Reality software, to illustrate mathematical concepts (Abdul Hanid et al, 2022). By manipulating variables and observing resultant changes, pupils can explore the relationships among mathematics, patterns, and functions.…”
Section: Activities Using Computers (Plugged In)mentioning
confidence: 99%
“…Simulation is another essential plugged-in activity, where pupils can utilize computer simulations, including Augmented Reality software, to illustrate mathematical concepts (Abdul Hanid et al, 2022). By manipulating variables and observing resultant changes, pupils can explore the relationships among mathematics, patterns, and functions.…”
Section: Activities Using Computers (Plugged In)mentioning
confidence: 99%
“…Lainufar et al (2020) emphasized that learning geometry with GeoGebra made geometry more visual. According to Abdul Hanid et al (2022), studies showed that teaching geometry using AR results in more high-achieving students than using textbooks. This is in line with Nazar et al (2020)'s finding that abstract concepts can be depicted more realistically by using AR.…”
Section: Related-workmentioning
confidence: 99%
“…Geometry is a branch of mathematics that explores measurement, relationships, and properties of points, angles, surfaces, lines, and solids (Abdul et al, 2022;Saxena, 2015). Within the realm of geometry, 3D geometry stands as one of basic sub-topics.…”
Section: The Concept Of 3d Geometrymentioning
confidence: 99%